Assessment Of Geothermal Prospective Area Using Integrated Multi-Spatial Data Analysis At Northeastern Nigeria - Abubakar, Yusuf (2022)
Spatial mapping of prospective geothermal zones is an important apparatus used in an initial exploration of renewable form of energy in the World. Previous studies have ignored the role of radiogenic heat sources in the construction of the models of their geothermal potential maps. Hence, left an incomplete study gap, where a vital aspect of earth’s heat is ignored. Therefore, the present study employed the radiogenic heat together with other parameters in mapping and analysis of areas of variable geothermal potentials using the GIS-based multicriteria evaluation approach. This study is the first geothermal study that accounted for the radiogenic heat in conjunction with other parameters for analysis of potential of this relatively not known geological location.